2003
DOI: 10.1074/jbc.m304597200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Myc Oncoprotein Limits the Growth of Human Melanoma Cells by Inducing Cellular Crisis

Abstract: Here, we show that inhibition of c-Myc causes a proliferative arrest of M14 melanoma cells through cellular crisis, evident by the increase in size, multiple nuclei, vacuolated cytoplasm, induction of senescence-associated ␤-galactosidase activity and massive apoptosis. The c-Myc-induced crisis is associated with decreased human telomerase reverse transcriptase expression, telomerase activity, progressive telomere shortening, glutathione (GSH), depletion and, increased production of reactive oxygen species. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Malignant melanoma has previously been shown to overexpress c-Myc, and re-establishing control of c-Myc levels in these tumors may have therapeutic effects (34)(35)(36)(37). Initial screening of a panel of seven melanoma cell lines showed that three cell lines, including A375 cells, were highly sensitive to the antiproliferative/ apoptotic effects of degrasyn (A375 IC 50 = 1.6 Amol/L).…”
Section: Resultsmentioning
confidence: 99%
“…Malignant melanoma has previously been shown to overexpress c-Myc, and re-establishing control of c-Myc levels in these tumors may have therapeutic effects (34)(35)(36)(37). Initial screening of a panel of seven melanoma cell lines showed that three cell lines, including A375 cells, were highly sensitive to the antiproliferative/ apoptotic effects of degrasyn (A375 IC 50 = 1.6 Amol/L).…”
Section: Resultsmentioning
confidence: 99%
“…Human melanoma cells have been shown to respond to the suppression of c-Myc expression by entering a crisis phase that involves inhibition of telomerase activity, telomere erosion, and apoptosis. 35) In addition, a positive correlation has been reported between inhibition of telomerase activity and apoptosis by curcumin in cancer cells, 36) although the signal activating apoptosis in the telomerase-inhibited cells has not been completely characterized. In this study, it appears that phosphorylation of ERK might be related to inhibition of telomerase and induction of apoptosis, though the connection between telomerase and apoptosis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Cells undergoing senescence are enlarged with a flat morphology, express acidic ␤-galactosidase activity, and show a permanent G 0 /G 1 arrest, whereas cells entering crisis are associated with apoptosis (31). Because in our study the overexpression of hTERT selectively suppressed the induction of apoptosis by 1,25(OH) 2 VD 3 without an effect on the hormone-induced cell cycle arrest, the down-regulation of hTERT by 1,25(OH) 2 VD 3 appears to drive OCa cells into a "crisis-like" status instead of senescence.…”
Section: Discussionmentioning
confidence: 99%